12 Reducing peri-operative opioids in ambulatory surgery – a quality improvement project using real-world data. (25th November 2019) - Low, Daniel; Martin, Lynn; Richards, Michael; Provost, Lloyd
Abstract : Background: The risk for adolescents developing persistent opioid use following surgery is 5%. Despite using multimodal analgesia and extensive regional anesthesia, 85% of our patients received opioids during and after surgery. Objectives: 1. Reducing opioids during and after surgery. 2. Maintain pain scores and post-operative analgesia requirements. 3. Maintain other outcome measures. 4. Accelerate Plan-Do-Study-Act (PDSA) cycle times. Methods: Teams completed multiple PDSA cycles, driven by real-world outcomes data, to reduce perioperative opioid administration. Clinical and operational measures, visualized as Statistical Process Control (SPC) charts, assessed the impact of different tests of change. Key interventions were derived from evidenced based medicine. SPC charts were used to determine real-world effectiveness. Results: From Jan 2018 to June 2019 our team achieved a 96% absolute reduction in perioperative opioid use for surgical patients (see figure 1 ). Post-operative oioid administration went from 14% to 2% (see figure 2A ). Post-operative nausea and vomiting (PONV) rate is now <0.001% (see figure 2B ). Recovery pain scores and length of stay were unchanged (see 2c and 2d). Improvement cycle times were reduced from 2 years to 2 months. Conclusions: 50 million Americans have surgery each year, 2 million of which develop persistent opioid use. The risk of persistent opioid use increases if patients are still taking opioids on day 5 postoperatively. Leveraging real-world data and SPC charts, PDSA cycles were significantly reduced. This reduction in opioid use creates a safer surgical journey and could help curb the opioid epidemic.